Tìm x, biết: x.( x – 4 ) + 1 = 3x – 5

Tìm x, biết:
x.( x – 4 ) + 1 = 3x – 5

2 bình luận về “Tìm x, biết: x.( x – 4 ) + 1 = 3x – 5”

  1. x(x-4)+1=3x-5
    => x^2 – 4x+1-3x+5=0
    => x^2 -7x +6=0
    => x^2 -x -6x +6=0
    => (x^2 -x) -(6x-6)=0
    => x(x-1)-6(x-1)=0
    => (x-6)(x-1)=0
    => [x6=0x1=0
    => [x=6x=1
    Vậy x in {1;6}

    Trả lời
  2. x(x-4)+1=3x-5
    => x^2-4x+1=3x-5
    => x^2-4x+1-3x+5=0
    => x^2-(4x+3x)+(1+5)=0
    => x^2-7x+6=0
    => x^2-x-6x+6=0
    => x(x-1)-6(x-1)=0
    => (x-6)(x-1)=0
    TH1:
    x-6=0
    => x=6
    TH2:
    x-1=0
    => x=1
    Vậy x={6;1}

    Trả lời

Viết một bình luận

Câu hỏi mới